2018
DOI: 10.18203/2394-6040.ijcmph20185251
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on vaccination default rates among children aged 9-24 months attending a static immunization clinic in urban and rural area of Bangalore

Abstract: Background: Immunization contributes significantly to the achievement of millennium development goal number 4 and is one of the eight elements of primary health care. Effective utilization of immunization services is associated with reduced infections in young children with immature immune system and improved child health outcome. The objectives of the study were to compare the default rates for vaccine doses in immunization schedule; to study the factors responsible for default; to describe the socio-demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…11,12 Our study found slight male preponderance (56.3%) which was in congruence with studies by, Kumar et al, Srikanth et al, Awasthi et al and Prinja et al at 56.5%, 56.6%, 55.7%, and 55.8%. 9,[13][14][15] More than two-thirds of participants in the present study belonged to joint family structure which was in line with research by Goyal et al 16 60.7% of children in our study ere of first birth order which was also observed by Dutta et al at 63.6%. 17 Institutional deliveries accounted for 95.2% which follows the pattern indicated in researches by Gill et al, Srikanth et al and Singh et al at 97.1, 98.8 and 95.1 percentages respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…11,12 Our study found slight male preponderance (56.3%) which was in congruence with studies by, Kumar et al, Srikanth et al, Awasthi et al and Prinja et al at 56.5%, 56.6%, 55.7%, and 55.8%. 9,[13][14][15] More than two-thirds of participants in the present study belonged to joint family structure which was in line with research by Goyal et al 16 60.7% of children in our study ere of first birth order which was also observed by Dutta et al at 63.6%. 17 Institutional deliveries accounted for 95.2% which follows the pattern indicated in researches by Gill et al, Srikanth et al and Singh et al at 97.1, 98.8 and 95.1 percentages respectively.…”
Section: Discussionsupporting
confidence: 90%
“…17 Institutional deliveries accounted for 95.2% which follows the pattern indicated in researches by Gill et al, Srikanth et al and Singh et al at 97.1, 98.8 and 95.1 percentages respectively. 13,18,19 Also it is higher than that in NFHS 4 district data for Agra. 20 Urban predominance similar to the current study was also observed by Sinha et al 21 Our study found low immunization coverage with 40.2% full immunization and 42.9% partial immunization.…”
Section: Discussionmentioning
confidence: 63%
“…The results of the study on hand showed that the majority of the studied parents had a moderate level of knowledge towards children immunization as shown in table (2). This findings was agree with the results in Yemen that was carried out a cross-sectional survey study on (400) parents, the study revealed that the (63.3%) of parents had a moderate level of knowledge [13] .…”
Section: Overall Assessment Of Parents' Knowledge Towards Immunizationsupporting
confidence: 87%
“…There are currently an estimated 19.5 million children in the world who have not received basic vaccine. Global vaccination coverage has stalled at 86%, with no significant improvements during the past year [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Various studies indicated that the main factors affecting defaulting from immunization were the age of the mother, maternal education, exposure to mass media, antenatal care (ANC), mother’s occupation, birthplace, birth order, place of residence, region, and distance to health care intuitions [ 18 24 ].…”
Section: Introductionmentioning
confidence: 99%